"People expect you to choose": Postcolonial hybridity in complex geographies of scaled diaspora identities. (June 2023) - Devadoss, Christabel
Hybridity in geography, specifically hybridity through a postcolonial lens, is often removed from postcolonial origins regarding geographic scale. I argue that postcolonial hybridity is key to situating geographic scalar identity within the context of postcolonial diasporas navigating competing ideas of nationalism and regionalism. Postcolonial hybridity as opposed to hybridity as hyphenated identity, provides a historically contingent lens useful to contextualizing lived scalar identities within diaspora communities, particularly in the United States, a nation founded on settler colonial ideologies. Drawing from 3 years of observational and interview-based research in the US Indian Tamil diaspora, I argue that scalar identity is a directly influenced by colonial constructions of race, identity, and ideas of nationalism. Drawing fromBhabha's (1994) concept of hybridity, I demonstrate how scalar identity can be reconceptualized with respect to postcolonial geographies of identity.